A Review of Tools to Screen for Social Determinants of Health in the United States: A Practice Brief - Marik Moen; Carla L. Storr; Danielle German; Erika Friedmann; Meg Johantgen (2020)
Increasingly, health care institutions are called on to address social determinants of health (SDH) given the connection to morbidity and mortality across populations. However, widespread implementation of screening for health-related social conditions (HRSC) is lagging. It is estimated that half of patients who have such needs may be missed by failure to screen routinely. Health care institutions face gaps in information related to screening tools. A review of tools that screen for HRSC at the individual level is needed to share readily available and applicable tools for integration in various settings, to communicate how tools are typically administered, and to assess whether tools capture domains corresponding with Institute of Medicine (IOM) core measures. To address these gaps, an unsystematic rapid review of the literature was conducted. In addition to peer-reviewed literature, Google, PubMed, and CINAHL databases and grey literature were searched with a focus on lead agencies or scholars in the field. English language publications from 2008–2018 with content related to SDH or health-related social condition screening tools were included. Nine commonly applied tools were selected and reviewed for content, setting, and method of administration. Fifteen common domains were identified and assessed for alignment with IOM recommendations and correspondence with the construct of social stability. This review consolidates essential information about HRSC screening tools in 1 place and provides practice, policy, and research recommendations to improve HRSC screening. This review is a practice brief that can help health care institutions and clinicians implement screening and interventions related to HRSC.